Geographies of Schooling - Jahnke, Holger; Kramer, Caroline; Meusburger, Peter; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This open access book explores the complex relationship between schooling as a set of practices embedded in educational institutions and their specific spatial dimensions from different disciplinary perspectives. It presents innovative empirical and conceptual research by international scholars from the fields of social geography, pedagogy, educational and social sciences in Germany, the United Kingdom, France, Czechia, Hungary, Austria, Switzerland, Norway and Canada. The book covers a broad range of topics, all examined from a spatial perspective: the governance of schooling, the transition processes of and within national school systems, the question of small schools in peripheral areas as well as the embeddedness of schooling in broader processes of social change. Transcending disciplinary boundaries, the book offers deep insights into current theoretical debates and empirical case studies within the broad research field encompassing the complex relationship between education and space.
Chapter 1. Territorial Governance of Schooling in Shrinking Regions -- Chapter 2. Local Educational Landscapes in Germany-Interfaces and Interlacings Between Education and Urban Development -- Chapter 3. School Autonomy Policies and the Changing Governance of Schooling -- Chapter 4. From Republican Spaces of Schooling to Educational Territories? The Problematic Emergence of Educational Territories in Post-Decentralized France -- Chapter 5. Ideology, Spatial Planning, and Rural Schools: From Interwar to Communist Hungary -- Chapter 6. Changing Structures and the Role of Education in the Development of the Educational System in Czechia -- Chapter 7. Securing Indigenous Dispossession Through Education: An Analysis of Canadian Curricula and Textbooks -- Chapter 8. Geopolitical Framings of Subalterity in Education: Compounding a Neoliberalized Welfare State -- Chapter 9. Bigger or Better? Research Based Reflections on the Cultural De-construction of Rural Schools in Norway-Meta Perspectives.-Chapter 10. A Multilevel View of Small Schools: Changing Systems in Baden-Württemberg and Vorarlberg -- Chapter 11. Small Rural Schools in Austria-Potentials and Challenges -- Chapter 12. Field and Terrain: The Micro-Politics of Community Leadership in Small, Rural Schools in England -- Chapter 13. Schools, Families and Social Reproduction -- Chapter 14. The Relationship Between School and Neighborhood-Child-Oriented Perspectives on Educational Locations -- Chapter 15. Redefining School: Educational Spaces for Adolescents' Engagement in Learning -- Chapter 16. Feminization of Teaching: Female Teachers at Primary and Lower Secondary Schools in Baden-Wuerttemberg, Germany-From its Beginnings to the Present.
Keywords: Human geography; Schools; Sociology, Urban; Sociology; Human Geography; School and Schooling; Urban Sociology; Sociology